2020
DOI: 10.1021/acsomega.0c02897
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin and Robust Micro–Nano Composite Coating for Implantable Pressure Sensor Encapsulation

Abstract: Implantable pressure sensors enable more accurate disease diagnosis and real-time monitoring. Their widescale usage is dependent on a reliable encapsulation to protect them from corrosion of body fluids, yet not increasing their sizes or impairing their sensing functions during their lifespans. To realize the above requirements, an ultrathin, flexible, waterproof while robust micro–nano composite coating for encapsulation of an implantable pressure sensor is designed. The composite coating is composed of a nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Nanostructural design also enhances the biocompatibility of 2D nanomaterials; typically, smaller and thinner materials exhibit higher biocompatibility. , Biocompatible coatings or encapsulations function as protective barriers that prevent direct contact between 2D nanomaterials and biological components. The biocompatibility of 2D nanomaterials is also improved by modifying their surface charge and introducing specific functional groups, which is verified by conducting extensive biological compatibility tests. The integration of 2D materials into biodegradable composites, drug-delivery systems, and surface-patterning techniques facilitates their applicability in tissue engineering, drug delivery, and regenerative medicine. , …”
Section: Properties Of 2d Nanomaterials Used In Healthcare Applicationsmentioning
confidence: 99%
“…Nanostructural design also enhances the biocompatibility of 2D nanomaterials; typically, smaller and thinner materials exhibit higher biocompatibility. , Biocompatible coatings or encapsulations function as protective barriers that prevent direct contact between 2D nanomaterials and biological components. The biocompatibility of 2D nanomaterials is also improved by modifying their surface charge and introducing specific functional groups, which is verified by conducting extensive biological compatibility tests. The integration of 2D materials into biodegradable composites, drug-delivery systems, and surface-patterning techniques facilitates their applicability in tissue engineering, drug delivery, and regenerative medicine. , …”
Section: Properties Of 2d Nanomaterials Used In Healthcare Applicationsmentioning
confidence: 99%
“…Rather than a topographical approach, a simple nano/micro coating was applied to a pressure sensor to improve interfacial adhesions and lifespan (Figure 4d). [ 86 ] The coating materials include a nanolayer of silane‐coupled molecules and a microlayer of parylene polymers. As shown in the SEM images (at 72 d after immersion in the simulated body fluid), the movable pressure sensor's surface with a two‐layer micro/nanocomposite coating (3.8 µm) showed a uniform, fine structure without surface defects.…”
Section: Nanomaterials For Implantable Devicesmentioning
confidence: 99%
“…Reproduced with permission. [ 86 ] Copyright 2020, American Chemical Society. e) Metal silicide alloy coating as an insoluble biofluid barrier and conductive electrical interface.…”
Section: Nanomaterials For Implantable Devicesmentioning
confidence: 99%
“…Furthermore, this design excellently resisted liquid interference, which has been proven effective in monitoring electronic eagles’ actions during artificial rainfall. On the contrary, Yao et al demonstrated the effectiveness of parylene as a microcomposite and nanocomposite water-resistant layer. Their investigations, which involved implanting sensors into the eyes of isolated pigs and living rabbits, underscored the superior performance of this material in protecting nanodevices, specifically those used for biomedical implants.…”
Section: Introductionmentioning
confidence: 99%